Development of TCM herb and immunosuppressant drug interaction database - Quek, Leona Yan Peng (2014)
Many forms of CAM treatments are widely used to treat illnesses but while they could be effective, their safety is rarely considered. One such risk includes the potential herb-drug interactions when TCM herbs are being consumed with conventional drugs that have a narrow therapeutic range such as immunosuppressants. This could often result in toxic effects or reduced therapeutic efficiency. The aim of this project is to develop a TCM herb-Western drug interaction database to be used as a source of reference for healthcare professionals in clinical evaluations. A list of various TCM herbs and Western drugs was selected and key search terms were formulated to search on various databases. Inclusion and exclusion criteria were abided and only relevant papers were analysed and categorised. A large number of in vivo and in vitro experiments and clinical studies have cast light on the possible interactions between TCM herbs and immunosuppressants at the pharmacokinetic and pharmacodynamic levels. The TCM herb-Western drug database is a potentially useful tool for healthcare professionals to make informed decisions and provide better treatment and diagnosis for patients.